Structured Classroom Intervention to Improve Learning Concentration of Students with ADHD in Inclusive Schools - Tri Gunadi (Journal of Educational Research and Learning Analytics, 2026)
Attention-Deficit/Hyperactivity Disorder frequently disrupts inclusive educational settings through executive function deficits, necessitating empirical intervention strategies. This study investigates the functional efficacy of structured classroom interventions on enhancing the learning concentration, operationalized as on-task behavior, among ADHD students within inclusive primary schools. Employing a quantitative single-subject experimental design utilizing a rigorous A-B-A-B withdrawal protocol, the research manipulated antecedent behavioral modifications. These modifications specifically integrated task segmentation, visual cues, and scheduled positive reinforcement. Visual analysis of observational data established a definitive causal nexus. Baseline concentration levels initially averaged an impaired 32.8%. Following the intervention, on-task behavior impressively surged to a peak of 72%. Crucially, the withdrawal phase precipitated a systemic regression down to 39.2%, firmly validating behavioral dependency on the intervention. A metric of 100% Percentage of Non-Overlapping Data unequivocally substantiates this intervention's profound magnitude. Ultimately, deploying prosthetic environmental scaffolding within inclusive frameworks is indispensable for mitigating neurobiological deficits and improving outcomes.